ATP-citrate lyase inhibitor improves ectopic lipid accumulation in the kidney in a db/db mouse model - Zhan, Zishun; Li, Aimei; Zhang, Wei; Wu, Xueqin; He, Jinrong; Li, Zhi; Li, Yanchun; Sun, Jian; Zhang, Hao (Frontiers in Endocrinology, 2022)
Aim We evaluated a novel treatment for obesity-related renal, an ATP-citrate lyase (ACL) inhibitor, to attenuate ectopic lipid accumulation (ELA) in the kidney and the ensuing inflammation. Materials and methods An ACL inhibitor was administered intragastrically to 12-week-old db/db mice for 30 days. The appearance of ELA was observed by staining kidney sections with Oil Red O, and the differences in tissue lipid metabolites were assessed by mass spectrometry. The anti-obesity and renoprotection effects of ACL inhibitors were observed by histological examination and multiple biochemical assays. Results Using the AutoDock Vina application, we determined that among the four known ACL inhibitors (SB-204990, ETC-1002, NDI-091143, and BMS-303141), BMS-303141 had the highest affinity for ACL and reduced ACL expression in the kidneys of db/db mice. We reported that BMS-303141 administration could decrease the levels of serum lipid and renal lipogenic enzymes acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), HMG-CoA reductase (HMGCR), and diminish renal ELA in db/db mice. In addition, we found that reducing ELA improved renal injuries, inflammation, and tubulointerstitial fibrosis. Conclusion ACL inhibitor BMS-303141 protects against obesity-related renal injuries.